Degree of discrepancy between self and other-reported everyday functioning by cognitive status: dementia, mild cognitive impairment, and healthy elders - Farias, Sarah Tomaszewski (2005)
BACKGROUND: Previous studies show individuals with dementia overestimate their cognitive and functional abilities compared to reports from caregivers. Few studies have examined whether individuals with Mild Cognitive Impairment (MCI) also tend to underestimate their deficits. In this study we examined whether degree of discrepancy between patient and informant-reported everyday functioning was associated with cognitive status. METHODS: The sample consisted of 111 ethnically diverse community-dwelling older adults (46 Caucasians and 65 Hispanic individuals), which was divided into four diagnostic categories: cognitively normal, MCI-memory impaired, MCI-non-memory impaired, and demented. Everyday functional abilities were measured using both a self-report and informant-report version of the Daily Function Questionnaire (DFQ). A Difference Score was calculated by subtracting patients’ DFQ score from their informants’ score. RESULTS: DFQ Difference Scores were significantly higher in the demented group compared to normals and both of the MCI groups. However, the Difference Scores for the MCI groups were not significantly different than the normals. Further, while patient reported everyday functioning did not differ among the four diagnostic groups, informant reported functional status was significantly different across all diagnostic groups except MCI-nonmemory impaired vs normals. Performance on objective memory testing was associated with informant-rated but not patient-rated functional status. Demographic characteristics of the patients and informants, including ethnicity, had no association with the degree of discrepancy between raters. CONCLUSIONS: Although there may be some mild functional changes associated particularly with the MCI-memory impaired subtype, individuals with MCI do not appear to under-report their functional status as can often been seen in persons with dementia.